Penyimpangan Prinsip Kerjasama dan Fungsi Tuturan dalam Gelar Wicara Mata Najwa Episode “Jokowi Diuji Pandemi” - Evi Martika D. Kasiahe (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
Mata Najwa Talkshow has become one of the most popular television programs, due to its popularity of the guests, also the significance of the information that can be dig through this program. The language usage in the conversation between host and guests becomes one of the interesting aspects to be researched. The words “mudik” and “pulang kampung” in the episode of “Jokowi Diuji Pandemi” have become a hot topic in the public. Either Jokowi or Najwa have their own intention (implicature) through what they were saying. This research utilizes pragmatic study that aims to describe the violation of cooperative principle and speech function that may cause implicature. This research utilizes the observation method with recording technique. The data analysis is conducted based on the pragmatic theory of Grice (1975) and Searle (1969). After research, it is found three forms flouting the cooperative principle and four of functions of speech in Mata Najwa Talkshow Episode “Jokowi Diuji Pandemi”.